SHORT COURSE PENINGKATAN PENGETAHUAN KADER DALAM RANGKA PENURUNAN STUNTING MELALUI KUNJUNGAN RUMAH - Sari, Rumita Ena; Herwansyah, Herwansyah; Putri, Fitria Eka; Mekarisce, Arnild Augina; Solida, Adila (Jurnal Salam Sehat Masyarakat (JSSM), 2025)
Knowledge enhancement is essential for behaviour change, as it increases an individual's awareness of the personal relevance of information. This service focuses on brief training on cadres' knowledge of Child Growth Monitoring (CPM), Child Development Monitoring (CDM), and Infant and Young Child Feeding (IYCF). This service aims to see the increase in knowledge with educational methods. Based on the results of the t test, the P value is 0.004, then the mean value of knowledge before education is 6.38 and increases to 11.52 after education and the standard deviationis 1.73 before education, then decreases to 0.64, which means that at 5% alpha there is a significant difference in improvement between the average knowledge of cadres before and after receiving training. It is hoped that cadres will be given periodic knowledge refreshers on Child Growth Monitoring (IYCF), Child Development Monitoring(PDA), and Infant and Young Child Feeding (IYCF), and other additional up-to-date material so that cadres can provide IEC to mothers about preventing stunting. Keywords: Stunting, Education, Cadres, Home, Visits